A five-layer co-extruded dry-process lithium battery separator and its preparation method and application
Through the combination of five-layer coextrusion technology and specific materials, the problem of mechanical strength dropping when the thickness of the dry lithium battery separator is reduced is solved, and a separator with high mechanical properties, puncture resistance and thermal stability is achieved, improving the safety and performance of the battery.
Patent Information
- Application Number
- CN202411896723.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing dry lithium battery separators reduce the thickness while reducing the mechanical strength, resulting in safety hazards and performance impacts.
The five-layer co-extrusion technology is adopted to reduce the extrusion amount and viscosity difference between the inner and outer layers through the synergistic effect of the outer layer, the transition layer and the inner layer, and enhance the mechanical strength of the diaphragm. The specific structure is A/B/C/B/A, where A is the outer layer, B is the transition layer, and C is the inner layer. It is prepared by a multi-layer coextrusion process using maleic anhydride copolystyrene grafted polypropylene, linear low-density polyethylene and styrene-methacrylic acid copolymer.
It realizes that while reducing the thickness of the diaphragm, it maintains or improves its mechanical strength, enhances the puncture resistance and thermal stability of the diaphragm, and reduces the safety hazards of battery short circuits.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery separators, and relates to a five-layer co-extruded dry-process lithium battery separator, a preparation method thereof, and an application thereof. Background Art
[0002] With the continuous deepening of the implementation of new energy policies, the research and development and production of new energy power batteries have become the focus of industry attention. Among them, lithium iron phosphate batteries (LFP) and ternary batteries (usually referring to nickel-cobalt-manganese or nickel-cobalt-aluminum lithium-ion batteries) have become popular choices in the market due to their unique performance advantages. Lithium iron phosphate batteries stand out in many application scenarios with their excellent stability and relatively low cost. This type of battery can not only provide a reliable energy storage solution, but also reduce costs to a certain extent, which is of great significance for promoting the popularization of new energy vehicles. Therefore, in recent years, the share of lithium iron phosphate batteries in the global market has shown an upward trend, especially in the Chinese market, where its application scope has continued to expand.
[0003] As the market share of lithium iron phosphate batteries grows, the demand for dry diaphragms used with them also increases. Lithium battery diaphragms are one of the most important components of liquid lithium-ion batteries and the material with the highest added value in lithium-ion batteries. Their cost accounts for 20-25% of the battery. Lithium battery diaphragms are mainly used between the positive and negative electrodes of lithium batteries to prevent direct contact between the positive and negative electrodes of lithium batteries and cause short circuits. The diaphragm can be used to store electrolytes, and the pores on it are used to allow Li + Freely pass between the positive and negative electrodes to realize the battery circuit. As one of the important components of lithium batteries, the dry diaphragm mainly prevents the positive and negative electrodes from directly contacting each other and causing short circuits, while allowing lithium ions to pass through to realize the charging and discharging functions. Compared with wet diaphragms, dry diaphragms have higher mechanical strength and better thermal stability, which makes them perform better in high temperature environments and helps to improve the overall safety of batteries. With the growth of global demand for clean energy and technological advances, lithium batteries will be more widely used in electric vehicles, fixed energy storage systems and even consumer electronics. In order to meet this growing demand, lithium battery manufacturers need to continuously improve production efficiency, reduce costs, and strive to develop more advanced dry diaphragm manufacturing processes. This development trend will not only promote the further maturity of the new energy industry, but also provide new development opportunities for related companies.
[0004] The manufacturing process of dry diaphragms is divided into dry single-pull process and dry double-pull process, and the mainstream is dry single-pull process. However, the mechanical strength of the diaphragm made according to the traditional dry single-pull process will gradually decrease as the thickness decreases, and the diaphragm is more likely to be punctured, causing safety problems. In addition, thinner diaphragms are more likely to melt when the battery reaction heats up, making the battery short circuit a greater safety hazard. Therefore, while reducing the thickness of the diaphragm, its mechanical strength must also be met. Most conventional methods are to coat the surface of the diaphragm to enhance the strength of the membrane and better adhere to the positive and negative electrodes. For example, Chongqing Enjie Newmi Technology Co., Ltd. disclosed in Chinese patent CN110048057B a surface-modified PMMA / PVDF mixed-coated lithium battery composite diaphragm and a preparation method thereof, and used a coupling agent to modify the surface of PMMA and PVDF to solve the problem of uneven distribution and easy sedimentation in the mixed coating of PMMA and PVDF, making the coating film smoother, enhancing the mechanical properties of the membrane and the absorption capacity of the electrolyte, and enhancing the ionic conductivity; Xinxiang Zhongke Technology Co., Ltd. disclosed in Chinese patent CN110591134A a modified PMMA and a preparation method thereof, and a method for preparing a high-energy flame-retardant lithium battery diaphragm using the modified PMMA, which is a modified PMMA produced by bonding the active groups in the guanidine salt with the polar groups of the PMMA copolymer precursor through the initiator AIBN, and then compounding the modified PMMA with polysiloxane and coating it on the diaphragm, thereby improving the mechanical properties and heat resistance of the diaphragm. The above patents all adopt a coating method, which can greatly enhance the mechanical properties of the diaphragm, but it will also increase the thickness of the diaphragm, and the coated particles will block the membrane pores, affecting the porosity and pore size of the coated diaphragm, thereby affecting the performance of the diaphragm.
[0005] At present, the thinning of lithium battery separators has become a new research direction, that is, reducing the thickness of the separator. In today's separator technology, the thickness of dry separators has changed significantly, from the original 32μm to the current 25μm, 20μm, and 16μm. The thinner the separator thickness, the shorter the distance lithium ions pass through the separator pores, which makes the battery internal resistance smaller, giving the battery better cycle performance and high energy density.
[0006] As the diaphragm becomes thinner, the reduction of its mechanical strength becomes an inevitable problem. To solve this challenge, multi-layer co-extrusion technology has shown great value in the production process of lithium battery diaphragms. This technology uses multiple extruders to melt and extrude different types of raw materials, and then converges them to the same die outlet through their respective flow channels. After cooling and compounding, a cast film is formed, which is then stretched to finally form a multi-layer diaphragm. Multi-layer co-extrusion technology is an integrated one-piece molding process. Unlike the traditional method of compounding multiple single-layer films into one or more films through hot pressing, it does not require additional coating steps to enhance the mechanical properties of the diaphragm. This process not only simplifies the production process and reduces labor and time costs, but also achieves the necessary mechanical strength while reducing the thickness of the diaphragm by combining the best characteristics of multiple resins.
[0007] Currently, three-layer co-extrusion technology has become the main process for producing 18μm and 12μm diaphragms. However, this technology encountered some challenges when trying to further reduce the thickness of the diaphragm to ≤10μm. During the production process, if the difference in extrusion volume between adjacent layers is too large, it may cause the following problems: first, the pressure difference between the layers will cause interlayer slippage; second, the overall symmetry imbalance will cause the film to curl or wrinkle; finally, when the viscosity of the multi-layer materials is very different, surface turbulence may occur between the layers, affecting the quality of the diaphragm.
[0008] To solve these problems, researchers are exploring ways to improve existing technologies or develop new materials to further reduce the thickness of the separator without affecting its mechanical strength. In addition, it is necessary to optimize the extrusion process to ensure the uniformity and stability between the layers to avoid the above problems. With the continuous advancement of technology, it is expected that multi-layer co-extrusion technology will play a more important role in improving the performance of lithium battery separators in the future. Summary of the invention
[0009] The present invention aims at the problems existing in the lithium battery separator in the prior art and provides a five-layer co-extruded dry-process lithium battery separator and a preparation method and application thereof.
[0010] One object of the present invention is achieved by the following technical solutions:
[0011] A five-layer co-extruded dry-process lithium battery separator, wherein the dry-process lithium battery separator adopts a symmetrical five-layer co-extruded structure of A / B / C / B / A;
[0012] A is an outer layer, and the raw materials include maleic anhydride copolymerized styrene grafted polypropylene;
[0013] B is a transition layer, and its raw materials include linear low-density polyethylene and polycaprolactone;
[0014] C is the inner layer, and the raw materials include styrene-methacrylic acid copolymer and homopolymer polypropylene;
[0015] The upper and lower surfaces of the inner layer are both in contact with the transition layer, and the side of the transition layer away from the inner layer is in contact with the outer layer.
[0016] The present invention provides a five-layer co-extruded dry-process lithium battery separator. Compared with the three-layer co-extruded structure, transition layers are added to the outer layer and the inner layer, and a symmetrical structure of A / B / C / B / A is adopted. The transition layer B is added to reduce the problem caused by the difference in extrusion amount between the A and C layers. At the same time, B is used as a transition layer to enhance the mechanical strength of the entire membrane.
[0017] The maleic anhydride copolymerized styrene grafted polypropylene is prepared from the following raw materials in parts by weight: 80-90 parts of polypropylene, 1-8 parts of maleic anhydride, 1-8 parts of styrene, and 1-4 parts of initiator. More preferably, it is 80-85 parts of polypropylene, 5-8 parts of maleic anhydride, 5-8 parts of styrene, and 2-4 parts of initiator. Still more preferably, it is 82 parts of polypropylene, 8 parts of maleic anhydride, 8 parts of styrene, and 2 parts of initiator.
[0018] The preparation method of maleic anhydride copolymerized styrene grafted polypropylene comprises the following steps: uniformly mixing maleic anhydride, styrene and polypropylene, adding an initiator, and melt-extruding and granulating at a temperature of 170-220° C. to obtain the maleic anhydride copolymerized styrene grafted polypropylene.
[0019] The present invention adopts maleic anhydride copolymerized styrene grafted polypropylene in the outer layer raw material, and strictly adjusts the raw material ratio. By adding polystyrene to participate in the polypropylene blended maleic anhydride grafted polypropylene system for granulation, compared with the single maleic anhydride grafted polypropylene diaphragm, the advantages are that the doping of polypropylene can help the modified material to be better dispersed in the polypropylene system, and the second is that maleic anhydride copolymerized styrene grafted polypropylene is a blend of styrene and maleic anhydride, which can effectively enhance the grafting rate, making up for the problem of low grafting rate of single maleic anhydride. Secondly, the grafting of polypropylene using the characteristics of maleic anhydride helps to improve the puncture resistance of the outer layer and enhance the heat resistance of the diaphragm to a certain extent. Secondly, the adhesiveness modified by maleic anhydride can be used as an appropriate adhesive between polar and non-polar materials, so that the diaphragm and the electrode can be better fitted and not easy to fall off, reducing the risk of direct contact between the positive and negative electrodes, and effectively enhancing the safety performance of the battery.
[0020] Preferably, the transition layer comprises the following raw materials in parts by weight: 80-90 parts of linear low-density polyethylene and 10-20 parts of polycaprolactone. More preferably, 85-90 parts of linear low-density polyethylene and 10-15 parts of polycaprolactone. Still more preferably, 87 parts of linear low-density polyethylene and 13 parts of polycaprolactone.
[0021] The present invention adopts linear low-density polyethylene and polycaprolactone in the raw materials of the transition layer, and optimizes the raw material ratio, which can play the role of bonding the inner and outer layers, so that the structure of the five-layer co-extruded diaphragm is complete. The linear low-density polyethylene and polycaprolactone materials both have high adhesion, and the high adhesion of the linear low-density polyethylene does not change with the change of temperature. Therefore, linear low-density polyethylene is selected as the basic material, and polycaprolactone with high adhesion, high impact resistance and thermal stability is doped at the same time, which can stabilize the thermal stability of the transition layer and cooperate with the outer layer to further enhance the puncture resistance of the diaphragm.
[0022] Preferably, the inner layer comprises the following raw materials in parts by weight: 30-40 parts of homopolypropylene and 60-70 parts of styrene-methacrylic acid copolymer. More preferably, 35-40 parts of homopolypropylene and 60-65 parts of styrene-methacrylic acid copolymer. Still more preferably, 37 parts of homopolypropylene and 63 parts of styrene-methacrylic acid copolymer.
[0023] The present invention uses styrene-methacrylic acid copolymer and homopolymer polypropylene in the inner layer raw materials. Homopolymer polypropylene has the characteristics of high regularity and high crystallinity, and can produce a large porosity under stretching conditions, helping ions to pass quickly and enhancing battery efficiency. However, due to its weak puncture resistance, styrene-methacrylic acid copolymer with high puncture resistance is selected for doping. Through the strictly adjusted doping ratio, while meeting the high porosity, it can be combined with the transition layer and the outer layer to further enhance the puncture resistance.
[0024] Preferably, the five-layer co-extruded dry-process lithium battery separator has a thickness of 5-11 μm, wherein the thickness ratio of the inner layer, the transition layer and the outer layer is 1-5:1-5:1-5, and more preferably 4:2:1.
[0025] Preferably, the outer layer has a melting index of 1.8-2.2 g / 10 min at 230°C and 2.16 kg, the transition layer has a melting index of 1.0-1.4 g / 10 min at 230°C and 2.16 kg, and the inner layer has a melting index of 0.4-0.8 g / 10 min at 230°C and 2.16 kg.
[0026] The second object of the present invention is achieved by the following technical solutions:
[0027] A method for preparing a five-layer co-extruded dry-process lithium battery separator, the method comprising the following steps: mixing the raw materials of an inner layer, a transition layer, and an outer layer respectively in three extruders, heating and melting them, injecting them into a five-layer co-extrusion die head, and performing cast film casting; then performing heat treatment and crystallization, cooling and annealing, and then cold stretching and hot stretching to obtain a five-layer co-extruded dry-process lithium battery separator.
[0028] Preferably, the melting temperature of the outer layer raw material is 170-190°C, the melting temperature of the transition layer raw material is 150-165°C, and the melting temperature of the inner layer raw material is 185-210°C.
[0029] Preferably, the temperature of the tape casting sheet is 60-100° C., and the thickness of the tape casting film obtained by the tape casting sheet is controlled at 10-15 μm.
[0030] Preferably, the heat treatment temperature is 120-150° C., and the heat treatment time is 1-20 hours.
[0031] Preferably, the cold stretching speed ratio is 1:(1.01-1.5), the hot stretching speed ratio is 1:(1.5-3.0), the cold stretching temperature is 50-70°C, and the hot stretching temperature is 100-130°C.
[0032] Preferably, the obtained five-layer co-extruded dry-process lithium battery separator can be cut into pieces according to the required width to obtain the final product.
[0033] The third object of the present invention is achieved by the following technical solutions:
[0034] Application of a five-layer co-extruded dry-process lithium battery separator in lithium batteries.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The present invention provides a five-layer co-extruded dry-process lithium battery separator, which uses preferred raw materials in the outer layer, transition layer and inner layer. The synergistic effect between the raw materials can greatly reduce the preparation thickness of the separator without affecting the mechanical properties of the separator. Combined with the five-layer co-extrusion technology, a five-layer co-extruded dry-process lithium battery separator with high mechanical properties, high stability and high precision is obtained.
[0037] 2. The present invention provides a five-layer co-extruded dry-process lithium battery separator, which uses maleic anhydride copolymerized styrene grafted polypropylene in the outer layer raw material. By grafting maleic anhydride copolymerized styrene on polypropylene, polar monomers are introduced to improve the interfacial bonding strength of the composite material. At the same time, the raw material can interact with the lithium battery electrolyte, improve the compatibility between non-polar polypropylene and the material and help improve the wettability of the separator to the electrolyte.
[0038] 3. The present invention provides a five-layer co-extruded dry-process lithium battery separator, in which polycaprolactone is doped in the linear low-density polyethylene raw material of the transition layer, which increases the polarity of the material and adjusts the compatibility; as a transition layer, it also acts as a binder, enhances the bonding force between the layers, reduces the difference in extrusion volume and viscosity between the inner and outer layers, so that the inner layer will not have a slip layer phenomenon, and the outer layer will not have a wrinkle phenomenon; at the same time, the doping of polycaprolactone makes the linear low-density polyethylene have high toughness, impact resistance and softness; polycaprolactone is a biodegradable polyester with flexibility and low glass transition temperature, which makes it maintain good flexibility at low temperatures. The mixed use of the two can give the diaphragm better mechanical properties, obtain a diaphragm material with excellent tensile strength and puncture resistance, so that it is not easy to break when subjected to external force; at the same time, the thermal stability of the diaphragm can be adjusted so that it can still maintain structural integrity in a high temperature environment, avoiding battery failure caused by thermal shrinkage. And the use of biodegradable polycaprolactone materials meets the requirements of sustainable development and has positive significance for reducing environmental impact.
[0039] 4. The present invention provides a five-layer co-extruded dry-process lithium battery separator, which uses styrene-methacrylic acid copolymer and homopolypropylene in the inner layer raw materials. The main purpose of homopolypropylene is its high regularity and high crystallinity characteristics, which can produce a larger porosity under stretching conditions, help ions pass through quickly, and enhance battery efficiency; styrene-methacrylic acid copolymer can improve the crystallization behavior and stress deformation of the separator, improve its mechanical properties, toughness and durability, reduce the risk of brittle fracture, and improve the electrochemical performance of the battery.
[0040] 5. The present invention adopts five-layer co-extrusion technology, and by introducing a transition layer, the difference in extrusion volume and viscosity between the inner and outer layers is reduced, so that the inner layer will not have a slip layer phenomenon, and the surface will not have wrinkles and the like. In the preparation method, after the molten material flows out through the five-layer co-extrusion die head, it is cast by casting, and then heat-treated, followed by cooling and crystallization, and then cold stretching, hot stretching and heat setting to form a mother roll. The obtained five-layer co-extruded diaphragm surface has strong mechanical properties, the molten material is stable, and the thickness control is highly accurate. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
[0042] The sources of raw materials in the following examples and comparative examples are as follows:
[0043] Styrene: Yueyang Huayu Chemical Co., Ltd.;
[0044] Maleic anhydride: Shandong Longhui Chemical Co., Ltd.;
[0045] Homopolymer polypropylene: Dongguan Baishun New Materials Co., Ltd.;
[0046] Linear low-density polyethylene: ExxonMobil Chemical Co.;
[0047] Polycaprolactone: Hunan Juren Chemical New Materials Technology Co., Ltd.
[0048] Example 1
[0049] The five-layer co-extruded dry-process lithium battery separator of this embodiment has a symmetrical five-layer co-extruded structure of A / B / C / B / A, and the thickness ratio of the five layers is 1:2:4:2:1. The total thickness of the obtained separator is 10 μm.
[0050] A is an outer layer, and the raw material of the outer layer is maleic anhydride copolymerized styrene grafted polypropylene, and the raw materials for its preparation are 82 parts of polypropylene, 8 parts of maleic anhydride, 8 parts of styrene, and 2 parts of initiator; the preparation method thereof comprises the following steps: dissolving maleic anhydride, styrene and polypropylene in toluene, adding initiator DCP and mixing evenly, and melt-extruding and granulating at 185°C to obtain the maleic anhydride copolymerized styrene grafted polypropylene; the melt index of the outer layer at 230°C and 2.16kg is 2.0g / 10min;
[0051] B is a transition layer, the raw materials of which are 87 parts of linear low-density polyethylene and 13 parts of polycaprolactone; the melt index of the transition layer at 230°C and 2.16kg is 1.3g / 10min;
[0052] C is the inner layer, and the raw materials of the inner layer are 37 parts of homopolymer polypropylene and 63 parts of styrene-methacrylic acid copolymer; the melt index of the inner layer at 230°C and 2.16kg is 0.5g / 10min.
[0053] The above five-layer co-extruded dry lithium battery separator preparation method comprises the following steps:
[0054] The raw materials of the three layers are mixed evenly in three extruders respectively, the melting temperature of the outer layer raw material is 185°C, the melting temperature of the transition layer raw material is 160°C, and the melting temperature of the inner layer raw material is 195°C. After heating and melting, they are squeezed into a five-layer co-extrusion die through five flow channels to form a molten cast body with a five-layer co-extruded composite structure of outer layer / transition layer / inner layer / transition layer / outer layer, and the temperature of the cast sheet is 70°C; then a five-layer co-extruded cast film is formed, and the thickness is controlled at 13μm; after heat treatment at 125°C for 12h, crystals are formed, and after cooling and annealing, cold stretching and hot stretching are performed, the cold stretching speed ratio is 1:1.2, the hot stretching speed ratio is 1:2.6, the cold stretching temperature is 60°C, and the hot stretching temperature is 124°C. After the crystals form membrane pores, a five-layer co-extruded dry-process lithium battery separator is obtained, and the total thickness of the obtained separator is 10μm.
[0055] Example 2
[0056] The five-layer co-extruded dry-process lithium battery separator of this embodiment is different from that of Embodiment 1 in that the raw material ratio in Embodiment 1 is replaced by the raw material ratio in this embodiment, and the preparation method of the separator is the same as that of Embodiment 1.
[0057] The five-layer co-extruded dry-process lithium battery separator of this embodiment has a symmetrical five-layer co-extruded structure of A / B / C / B / A, and the thickness ratio of the five layers is 1:2:4:2:1. The total thickness of the obtained separator is 10 μm;
[0058] A is the outer layer, the outer layer raw material is maleic anhydride copolymerized styrene grafted polypropylene, and its preparation raw materials are 83 parts of polypropylene, 8 parts of maleic anhydride, 8 parts of styrene, and 3 parts of initiator; the preparation method is the same as that of Example 1;
[0059] B is a transition layer, and the raw materials of the transition layer are 90 parts of linear low-density polyethylene and 10 parts of polycaprolactone;
[0060] C is the inner layer, and the raw materials of the inner layer are 40 parts of homopolymer polypropylene and 60 parts of styrene-methacrylic acid copolymer.
[0061] The rest is the same as in Example 1.
[0062] Example 3
[0063] The five-layer co-extruded dry-process lithium battery separator of this embodiment is different from that of Embodiment 1 in that the raw material ratio in Embodiment 1 is replaced by the raw material ratio in this embodiment, and the preparation method of the separator is the same as that of Embodiment 1.
[0064] The five-layer co-extruded dry-process lithium battery separator of this embodiment has a symmetrical five-layer co-extruded structure of A / B / C / B / A, and the thickness ratio of the five layers is 1:2:4:2:1. The total thickness of the obtained separator is 10 μm;
[0065] A is the outer layer, the outer layer raw material is maleic anhydride copolymerized styrene grafted polypropylene, and its preparation raw materials are 85 parts of polypropylene, 5 parts of maleic anhydride, 5 parts of styrene, and 2 parts of initiator; the preparation method is the same as that of Example 1;
[0066] B is a transition layer, and the raw materials of the transition layer are 85 parts of linear low-density polyethylene and 15 parts of polycaprolactone;
[0067] C is the inner layer, and the raw materials of the inner layer are 35 parts of homopolymer polypropylene and 65 parts of styrene-methacrylic acid copolymer.
[0068] The rest is the same as in Example 1.
[0069] Example 4
[0070] The five-layer co-extruded dry-process lithium battery separator of this embodiment is different from that of Embodiment 1 in that the raw material ratio and preparation thickness in Embodiment 1 are replaced by the raw material ratio and preparation thickness in this embodiment, and the preparation method of the separator is the same as that of Embodiment 1.
[0071] The five-layer co-extruded dry-process lithium battery separator of this embodiment has a symmetrical five-layer co-extruded structure of A / B / C / B / A, and the thickness ratio of the five layers is 0.5:2.5:5:2.5:0.5. The total thickness of the obtained separator is 11 μm.
[0072] A is the outer layer, the outer layer raw material is maleic anhydride copolymerized styrene grafted polypropylene, and its preparation raw materials are 88 parts of polypropylene, 4 parts of maleic anhydride, 4 parts of styrene, and 1 part of initiator; the preparation method is the same as that of Example 1;
[0073] B is a transition layer, and the raw materials of the transition layer are 83 parts of linear low-density polyethylene and 17 parts of polycaprolactone;
[0074] C is the inner layer, and the raw materials of the inner layer are 33 parts of homopolypropylene and 67 parts of styrene-methacrylic acid copolymer.
[0075] The rest is the same as in Example 1.
[0076] Comparative Example 1
[0077] The lithium battery separator of this comparison is different from that of Example 1 in that the outer layer material is polypropylene, and maleic anhydride copolymerized styrene is not used for grafting, and the rest is the same as that of Example 1.
[0078] Comparative Example 2
[0079] The lithium battery separator of this comparison is different from that of Example 1 in that the inner layer material is homopolymer polypropylene and no styrene-methacrylic acid copolymer is used for doping. The rest is the same as that of Example 1.
[0080] Comparative Example 3
[0081] The lithium battery separator of this comparison is different from that of Example 1 in that the raw material of the transition layer is linear low-density polyethylene, and polycaprolactone is not added. The rest is the same as that of Example 1.
[0082] Comparative Example 4
[0083] The lithium battery separator of this comparison is different from that of Example 1 in that the outer layer raw material is polypropylene, and maleic anhydride copolymerized styrene is not used for grafting; the transition layer raw material is linear low-density polyethylene, and polycaprolactone is not added; the inner layer raw material is homopolymerized polypropylene, and styrene-methacrylic acid copolymer is not used for doping; the rest is the same as Example 1.
[0084] Comparative Example 5
[0085] The lithium battery separator of this comparison is different from that of Example 1 in that no transition layer is provided, and the structure is a three-layer co-extruded structure of A / C / A, and the rest is the same as that of Example 1.
[0086] The dry-process diaphragms of the above-mentioned embodiments and comparative examples were cut into pieces of 200 mm×300 mm, and then subjected to relevant mechanical and thermal property tests. The specific test results are shown in Table 1.
[0087] Table 1 Performance test results of examples and comparative examples
[0088] .
[0089] As shown in Table 1, it can be seen from Examples 1 to 4 that the five-layer co-extruded dry-process lithium battery separator prepared using the technical solution of the present invention has excellent mechanical properties and effectively improves the liquid absorption and retention capacity of the separator and the positive electrode bonding strength.
[0090] It can be seen from Comparative Examples 1 to 5 that the lithium battery separators prepared in Comparative Examples 1 to 4 without the technical solution of the present invention, including the outer layer without maleic anhydride copolymerization of styrene to graft polypropylene / the transition layer without styrene-methacrylic acid copolymer to dope homopolypropylene / the inner layer linear low-density polyethylene without adding polycaprolactone, all have decreased in mechanical properties, liquid absorption rate and bonding strength. Comparative Example 5 does not use the five-layer co-extrusion structure of the present invention, resulting in a large difference in extrusion volume between layers A and C, which reduces the mechanical strength of the separator and significantly reduces the overall performance.
[0091] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0092] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0093] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A five-layer co-extruded dry-process lithium battery separator, characterized in that: The dry-process lithium battery separator adopts a symmetrical five-layer co-extrusion structure of A / B / C / B / A; A is an outer layer, and the raw materials include maleic anhydride copolymerized styrene grafted polypropylene; B is a transition layer, and its raw materials include linear low-density polyethylene and polycaprolactone; C is the inner layer, and the raw materials include styrene-methacrylic acid copolymer and homopolymer polypropylene; The upper and lower surfaces of the inner layer are in contact with the transition layer, and the side of the transition layer away from the inner layer is in contact with the outer layer; The maleic anhydride copolymerized styrene grafted polypropylene is prepared from the following raw materials in parts by weight: 80-90 parts of polypropylene, 1-8 parts of maleic anhydride, 1-8 parts of styrene, and 1-4 parts of initiator; The transition layer comprises the following raw materials in parts by weight: 80-90 parts of linear low-density polyethylene and 10-20 parts of polycaprolactone; The inner layer comprises the following raw materials in parts by weight: 30-40 parts of homopolypropylene and 60-70 parts of styrene-methacrylic acid copolymer.
2. A five-layer co-extruded dry-process lithium battery separator according to claim 1, characterized in that: The preparation method of maleic anhydride copolymerized styrene grafted polypropylene comprises the following steps: uniformly mixing maleic anhydride, styrene and polypropylene, adding an initiator, and melt-extruding and granulating at a temperature of 170-220° C. to obtain the maleic anhydride copolymerized styrene grafted polypropylene.
3. A five-layer co-extruded dry-process lithium battery separator according to claim 1, characterized in that: The five-layer co-extruded dry-process lithium battery separator has a thickness of 5-11 μm, wherein the thickness ratio of the inner layer, the transition layer and the outer layer is 1-5:1-5:1-5.
4. A five-layer co-extruded dry-process lithium battery separator according to claim 1, characterized in that: The outer layer has a melting index of 1.8-2.2 g / 10 min at 230° C. and 2.16 kg, the transition layer has a melting index of 1.0-1.4 g / 10 min at 230° C. and 2.16 kg, and the inner layer has a melting index of 0.4-0.8 g / 10 min at 230° C. and 2.16 kg.
5. A method for preparing a five-layer co-extruded dry-process lithium battery separator according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: mixing the raw materials of the inner layer, the transition layer and the outer layer respectively in three extruders, injecting them into a five-layer co-extrusion die head after heating and melting, and performing cast film casting; then performing heat treatment and crystallization, cooling and annealing, and then performing cold stretching and hot stretching to obtain a five-layer co-extruded dry-process lithium battery separator.
6. The preparation method according to claim 5, characterized in that: The melting temperature of the outer layer raw material is 170-190°C, the melting temperature of the transition layer raw material is 150-165°C, and the melting temperature of the inner layer raw material is 185-210°C; The temperature of the tape casting sheet is 60-100° C., and the thickness of the tape casting film obtained by the tape casting sheet is controlled to be 10-15 μm.
7. The preparation method according to claim 5, characterized in that: The heat treatment temperature is 120-150°C and the heat treatment time is 1-20h; The cold stretching speed ratio is 1:(1.01-1.5), the hot stretching speed ratio is 1:(1.5-3.0), the cold stretching temperature is 50-70°C, and the hot stretching temperature is 100-130°C.
8. Use of a five-layer co-extruded dry-process lithium battery separator as described in any one of claims 1 to 4 in a lithium battery.
Citation Information
Patent Citations
Surface-modified PMMA / PVDF hybrid coated lithium battery composite separator and its preparation method
CN110048057B
Modified PMMA, preparation method thereof and preparation method of high-specific capacity flame-retardant lithium battery membrane by using modified PMMA
CN110591134A
Transition metal capture diaphragm as well as preparation method and application thereof
CN114696036A
Five-layer co-extrusion diaphragm and preparation method thereof
CN115411458A
Cited By
A dry-process lithium battery separator, its preparation method and application
CN122823018A